Evaluation of the papilla level adjacent to implants placed in fresh, healing or healed sites: A systematic review - Goiato, M. C. [UNESP]; de Medeiros, R. A. [UNESP]; da Silva, E. V.F. [UNESP]; dos Santos, D. M. [UNESP] (Elsevier, 2017)
A better understanding of factors that can lead to papilla formation or recession, such as the type of site where the implant was placed, is of fundamental importance to the aesthetic success of the rehabilitation. The aim of this study was to perform a systematic review of the literature regarding the formation or recession of papilla adjacent to implants placed in fresh, healing or healed sites. The protocol for this study was registered in the PROSPERO database (registration number CRD 42016033784). An electronic search was performed by two independent reviewers who applied the inclusion and exclusion criteria on the PubMed/MEDLINE, Scopus, and Embase databases from January 2005 up to February 2016. The initial screening yielded 1,065 articles, from which 15 were selected for a systematic review after applying the inclusion and exclusion criteria. Nine studies compared fresh and healed sites, four studies compared healing and healed sites, one study compared fresh and healing sites, and one study analysed all three sites. The majority of studies identified by this systematic review showed no difference between groups after the longer follow-up period. The sites where the implants were placed did not have a long-term influence on papilla formation or recession.
Keywords: dental implants; dental papillae; single-tooth implants